PENURUNAN KONSENTRASI COD DAN FENOL AIR LUMPUR LAPINDO DENGAN METODE OKSIDASI FENTON DAN UV - Evy Hendriarianti (Purifikasi, 2007)
This research was carried out to investigate the removal of COD and phenol sludge filtrate by Fenton oxidation and UV after the treatment of coagulation-flocculation-sedimentation. Variation of treatments included UV intensity, H2O2 and FeSO4 concentration, and illumination time was 3 hours. The results showed that 92,71 % of COD removal and 100% of phenol removal (undetectable phenol) occurred at 36 Watt of UV, 250 mg/L of H2O2 and at 36 Watt of UV, 500 mg/L of H2O2. While 84,24% of COD removal occurred at Fenton variation of 500 mg/L of H2O2 : 100 mg/L of FeSO4 and 72 watt of UV light. Phenol removal of 98,84 % occurred at Fenton variation of 500 mg/L of H2O2 : 100 mg/L of FeSO4. and 36 watt of UV light.